2011
DOI: 10.1063/1.3554211
|View full text |Cite
|
Sign up to set email alerts
|

Very accurate potential energy curve of the LiH molecule

Abstract: We present very accurate calculations of the ground-state potential energy curve (PEC) of the LiH molecule performed with all-electron explicitly correlated Gaussian functions with shifted centers. The PEC is generated with the variational method involving simultaneous optimization of all Gaussians with an approach employing the analytical first derivatives of the energy with respect to the Gaussian nonlinear parameters (i.e., the exponents and the coordinates of the shifts). The LiH internuclear distance is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 29 publications
4
66
0
Order By: Relevance
“…Special investigations were devoted to dipole moments 24,25 and ionic states of LiH 26,27,28 . Recently, Tung et al 29 and Holka et al 30 performed very accurate calculations of the ground and some excited state potential curves.…”
Section: In 2006mentioning
confidence: 99%
“…Special investigations were devoted to dipole moments 24,25 and ionic states of LiH 26,27,28 . Recently, Tung et al 29 and Holka et al 30 performed very accurate calculations of the ground and some excited state potential curves.…”
Section: In 2006mentioning
confidence: 99%
“…The above formula represents a general case of the expectation value of δ 3 ((b ⊗ I 3 ) T r − ξ) and, with an appropriate choice of vector (b ⊗ I 3 ), it can be used to calculate matrix elements of operators representing δ 3 (r i j ) in the Darwin termĤ I I d2 (13) and δ 3 (r ia ) in the Darwin termĤ I I d1 (12). The matrix elements ⟨δ 3 (r i j )⟩ and ⟨δ 3 (r ia )⟩ are obtained by setting bb T ⊗ I 3 = J i j and bb T ⊗ I 3 = J ii , respectively.…”
Section: B Darwin Correctionmentioning
confidence: 99%
“…6 They showed that careful optimization of the non-linear parameters of the ECGs not only yields accurate nonrelativistic energies but also very well converged leading relativistic corrections, even in the traditional approach employing the Pauli Hamiltonian. Recently we have used ECGs in very accurate calculations of some two-, three-, and four-electron systems, H + 3 , 7-10 LiH + , 11 LiH, 12 He + 2 , 13 and (H 2 ) 2 . 14 The calculations produced the most a) Electronic address: monika@fizyka.umk.pl b) Electronic address: epalikot@doktorant.umk.pl c) Electronic address: ludwik@email.arizona.edu accurate nonrelativistic ground-state potential-energy surfaces (PESs) for these systems ever calculated.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations are performed employing the basis sets containing 2400 ECGs generated in Ref. 9 As there have not been any previous high-accuracy calculations of the OO correction for a four-electron molecular system before, no comparison can be made in this case. However, as the value of the correction changes by about 20% when the internuclear distance increases from 2 to 10 a.u., it can be expected to have a non-negligible effect on the rovibrational transition energies when the correction is included in the LiH PES.…”
Section: Numerical Testsmentioning
confidence: 99%
“…With this the upper part of the rovibrational spectrum of this system (in the 20 000-30 000 cm −1 spectral range) will be studied. More exact determination of the rovibrational spectrum will also be performed for the LiH molecule, 9 as well as for other small molecules with more than two nuclei and/or more than two electrons (e.g., H 3 , LiH + 2 , and HeH − ). In Sec.…”
Section: Introductionmentioning
confidence: 99%